Oxidation of ferrocytochrome c by mitochondrial cytochrome c oxidase. - Errede, B (1976)
Attempts to rationalize the kinetics of cytochrome c oxidation catalyzed by solubilized mitochondrial cytochrome c oxidase (ferrocytochrome c:oxygen oxidoreductase, EC 1.9.3.1) have been based on assumptions of productive complex formation (Michaelis-Menten approach). However, the range of substrate concentrations used has not, in general, been sufficient to establish a general rate equation. Data adequate to derive such a rate expression are presented, as well as a method for estimation of constants which appear in the rate law deduced and reported herein. It is shown that either of two types of mechanisms, one assuming productive complex formation, as opposed to the other postulating dead-end complex formation, accurately predict the rate equation as deduced from experiment.